A MODEL FOR ENTERPRISES’ ENVIRONMENTAL SCANNING - Tudor NISTORESCU; Catalin Mihail BARBU (Management & Marketing)
Today’s environment determines companies to use scanning activities inorder to seize the opportunities and to avoid the threats. Individual factorsand organizational factors influence the scanning behavior. The examinationof the environment can be presented in a model based on environmentanalyzability and organizational intrusiveness.